2012
DOI: 10.1007/s10535-012-0124-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in protein pattern during different developmental stages of somatic embryos in chickpea

Abstract: Mature embryonic axes were used for chickpea (Cicer arietinum L.) regeneration via somatic embryogenesis. Qualitative and quantitative estimation of protein profile during somatic embryogenesis by SDS-PAGE and densitometric analysis showed differential expression of various storage proteins at different stages of somatic embryo development, which was compared with the profile of developing seeds. Total protein content in somatic embryos of chickpea increased from globular stage [2.9 μg mg -1 (f.m.)] to cotyled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
(26 reference statements)
1
19
0
Order By: Relevance
“…The latter has only previously been identified in Pinus strobus (Klimaszewska et al 2004); it is quite similar to 11S legumin-like protein, which is a closely related member (though with a slight difference in size) of the globulin family. In angiosperm species, specific globulin-like proteins have been reported to accumulate in SEs; they include citrin in Citrus sinensis (Koltunow et al 1996) and convicilin in Pisum sativum (Mishra et al 2012). …”
Section: Quality Of Cotyledonary Ses Did Not Vary As a Function Of Thmentioning
confidence: 99%
“…The latter has only previously been identified in Pinus strobus (Klimaszewska et al 2004); it is quite similar to 11S legumin-like protein, which is a closely related member (though with a slight difference in size) of the globulin family. In angiosperm species, specific globulin-like proteins have been reported to accumulate in SEs; they include citrin in Citrus sinensis (Koltunow et al 1996) and convicilin in Pisum sativum (Mishra et al 2012). …”
Section: Quality Of Cotyledonary Ses Did Not Vary As a Function Of Thmentioning
confidence: 99%
“…Maturation is a crucial step for the success of somatic embryogenesis. Essential processes of this stage include cell expansion, differentiation and accumulation of reserve substances necessary for germination and regeneration of somatic embryos [19]. In the present study, embryogenic calli with globular stage somatic embryos were observed under stereomicroscope after 60-70 days of culturing (Plate.…”
Section: Resultsmentioning
confidence: 91%
“…However, a study by Rani et al (2009) reported that protein of about 22 KDa was found in somatic and zygotic embryo stage of peanut. Mishra et al (2012) also reported that in late stage of somatic embryo of chickpea, there was a protein ranged from 22-24 KDa identified as Late Embryogenesis Abundant (LEA) protein, or Legumin β that has a molecular weight of about 20 KDa. There was 37.69 KDa protein found at somatic embryo sample.…”
Section: Materials and Tissue Culture Conditionsmentioning
confidence: 97%
“…That protein band was also found in embryo of P. taeda (Brownfield et al, 2007) that was later predicted as storage protein. Mishra et al (2012) reported that storage protein in chickpea that was between 34-37 KDa was associated with vicilin minor subunit that appeared at different stages of somatic embryo. However, study by Tonietto et al (2012) reported that a protein of about 37 KDa in somatic embryo of coffee was later identified as Glyceraldehide 3-phosphate dehydrogenase; a kind protein correlated with glycolisis, and also to be involved in plant defence reaction against reactive oxygen species (ROS) such as hydrogen peroxide (Hancock et al, 2005).…”
Section: Materials and Tissue Culture Conditionsmentioning
confidence: 99%